The association of ICAM-1 detected by immunohistochemical staining with triple negative and non-triple negative breast carcinoma - Chong, Choi Yen; Sabreena Safuan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Metastasis of tumour cell greatly contributes to the cause of mortality. Tumour-associated macrophage (TAM) and the intercellular adhesion molecule 1 (ICAM-1) were associated with metastases of breast carcinoma. However, the relationship between lymphatic vessel densities and invasion with TAM and ICAM-1 remained unclear. The aim of this study was to investigate the relationship of lymphovascular densities and invasions with patient’s clinicopathological data. The roles of TAM and ICAM-1 influencing lymphovascular invasions were also investigated. Haematoxylin and eosin (H&E) and immunohistochemical (IHC) staining on a consecutive section of 37 formalin fixed-paraffin embedded (FFPE) breast invasive carcinoma samples were carried out. The D2-40, CD34, CD163, and ICAM-1 antibodies were used to stain lymphatic vessel, blood vessel, TAM, and ICAM-1 receptor, respectively. The total lymphatic vessel density (LVD) was significantly reduced on increased tumor size (p=0.045). The increase of intra-tumoral LVD and lymphatic vessel invasion (LVI) was significantly associated with human epidermal growth factor receptor 2 (HER2) negative status (p=0.022 and p=0.05, respectively). The percentage of LVI was higher than blood vessel invasion (BVI) in 18.5%. Lymphovascular invasions detected in H&E were missed in 49.76% compared with those detected in IHC-stained tissues (206/410). ICAM-1 scores were significantly associated with non-triple negative breast cancer (non-TNBC) (p=0.008). ICAM-1 is significantly overexpressed on non-TNBC sample. Therefore, ICAM-1 might be clinically useful as a targeted molecule for non-TNBC patients. In histological reporting, in addition to H&E staining, IHC staining using D2-40 and CD34 should be considered to increase the accuracy of diagnosis.